EXPANDING LEARNING HORIZONS: EXPLORING GARDNER’S MULTIPLE INTELLIGENCES AND THEIR CONTRIBUTION TO EDUCATION - Useini, Arafat; Rizvançe Matsani, Şehida (International Scientific Journal Vision, 2025)
Howard Gardner’s Theory of Multiple Intelligences (MI), introduced in the early 1980s, has profoundly influenced contemporary educational practices by challenging traditional, singular conceptions of intelligence. The theory posits that individuals possess a variety of cognitive capacities, each reflecting unique ways of learning and understanding the world. Gardner initially proposed seven intelligences, later expanding the framework to eight, encompassing verbal-linguistic, logical-mathematical, visual-spatial, intrapersonal, interpersonal, bodily-kinesthetic, musical-rhythmic, and naturalist intelligences. Each intelligence dimension reflects distinct skills, learning preferences, and modes of interaction with the environment, emphasizing the multifaceted nature of human cognition. This paper examines the principles underlying MI theory, its implications for curriculum design, and practical strategies for fostering diverse intelligences in educational settings. Recommendations include curriculum integration, individualized learning approaches, interdisciplinary activities, teacher training, and alternative assessment methods. The adoption of MI-based practices enhances student engagement, motivation, and holistic development, while promoting personalized and inclusive learning environments. Furthermore, integrating MI theory into teaching and assessment practices supports educational innovation and long-term societal benefits by preparing students with diverse cognitive, creative, and social skills. Overall, the theory of multiple intelligences offers educators and policymakers a framework for cultivating versatile, well-rounded learners who can thrive in complex and dynamic learning contexts.